Odpowiedź:
a)[tex]\sqrt{3}x\sqrt{5}\sqrt{15}=\sqrt{225}=15[/tex]
b)[tex]\sqrt{\frac{4}{5} }x\sqrt{0,6}x\sqrt{12}=\sqrt{\frac{4}{5}x0,6x12 } =\sqrt{\frac{4}{5}x\frac{3}{5}x12 }=\sqrt{\frac{144}{25} }=\frac{12}{5}=2\frac{2}{5}[/tex]
c)
[tex]\sqrt[3]1{\frac{1}{5} } -\sqrt[3]{2,5}x\sqrt[3]{1\frac{1}{8} } =\sqrt[3]{\frac{6}{5} }-\sqrt[3]{2,5}x\sqrt[3]{\frac{9}{8} }=\frac{\sqrt[3]{6} }{\sqrt[3]{5} }-\sqrt[3]{2,5x\frac{9}{8} }=\frac{\sqrt[3]{6x25} }{5}-\sqrt[3]{\frac{45}{16} }=\frac{\sqrt[3]{150} }{5}-\frac{\sqrt[3]{45} }{\sqrt[3]{16} }=\frac{\sqrt[3]{150} }{5}-\frac{\sqrt[3]{x\45} }{2\sqrt[3]{2} }=\frac{\sqrt[3]{45x2^{2} } }{4}=\frac{\sqrt[3]{150} }{5}-\frac{\sqrt[3]{45x4} }{4}=\frac{\sqrt[3]{150} }{5}-\frac{\sqrt[3]{180} }{4}[/tex]
Szczegółowe wyjaśnienie: